PENGARUH STRES KERJA DAN KONFLIK KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PEMBERDAYAAN MASYARAKAT DAN DESA PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN BUOL - Alfansyah Fathur; Elfirah Salviah; Indahsari A. Sabora (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
This study aims to determine the effect of work stress and work conflict on employee performance at the Office of Community Empowerment and Village Women's Empowerment and Child Protection Buol Regency. This research is included in a descriptive study using a quantitative approach. Office of Community Empowerment and Village Women's Empowerment and Child Protection Buol Regency. The number of samples used was 41 employees. The sampling technique was saturated sample. The instrument test used statistical analysis techniques and classical assumption tests. The analytical technique used was multiple linear regression. shows that: (1) work stress partially affects employee performance, (2) work conflict partially affects employee performance, (3) work stress and work conflict simultaneously affect employee performance.